PROFIL STRATEGI BELAJAR SRL KOMPONEN KOGNITIF DALAM MEMPERSIAPKAN UJIAN SOCA SELAMA MASA PEMBELAJARAN TATAP MUKA TERBATAS - Widiartini, Catharina; Hidayah, Arfi Nurul; Ardansyah, Marsya Bunga Dis (Medical and Health Journal, 2023)
Background: SOCA is an assessment method which tests students' critical thinking, clinical reasoning, and communication skills. SRL (self-regulated learning) cognitive component is a crucial learning-strategies which is useful in processing and storing information on preparing SOCA. SRL determines presage factors in learning environment change. The learning process has changed since the COVID-19 pandemic, which was originally fully online to PTMT. These environmental changes regulate an important role in the SOCA preparation process; thus, this profile of the learning process is not only prominent for monitoring and evaluating in policy making by institution, but also for self-evaluating by respondents. Objective: To find profile of SRL learning strategies for cognitive components in preparing SOCA from FK Unsoed students’ during limited face-to-face learning method in 2021/2022. Methods: This quantitative-observational-descriptive study uses primary data from a questionnaire "SRL Learning Strategies in Limited Face-to-Face Learning Period" by 199 undergraduate-student (of batch 2019, 2020, and 2021). The results are presented in tables and frequency-distribution diagrams based on the sub-components of learning strategies and frequency of use. Results: Most (70.35%) of the respondents were women with an average age of 19.6 years. The majority of respondents always apply rehearsal learning strategies and quite often apply elaboration, organizing, and critical thinking learning strategies. The smallest proportion of application frequency types is "never". Conclusion: The percentage of implementation of "rarely " and "never" are less than the percentage of implementation of "always" and "often".